D-dimer negative pulmonary embolism - M., Dhananjaya; Meti, Kirankumar; Parakh, Rajendrakumar (International Journal of Advances in Medicine, 2018)
Background: Pulmonary embolism (PE), is one of the major cardiovascular causes of death. Pulmonary embolus (PE) can be fatal but is often treatable if recognized early. Unfortunately, the clinical presentation of PE is often variable and misleading mimicking other illnesses and hence known as "the Great Masquerader," making diagnosis difficult. The D-dimer assay has recently come into favour as a method to exclude PE; however, this test has an acceptable safety margin only in low-risk populations. Methods: Present study included 35 patients with clinical suspicion of pulmonary embolism admitted at the tertiary care hospital of North Karnataka during the period from October 2016 to September 2017. Patients were classified according to final diagnosis by CT Pulmonary Angiography into 28 cases positive for PE (80%) and 7 cases negative for PE (20%). Results: Present study included 35 cases suspected to have PE (26 males and 9 females). Their age ranged from 33 to 72 years, with a mean age 48.9 ±14.2 years. 28 cases positive for PE (80%) and 7 cases negative for PE (20%). The mean age of positive and negative PE cases was 48.1±11.2 and 46.4±8.8 respectively. Results of D-dimer test were positive in 10 cases (35.7%) and were negative in 18 cases (61.3 %) of PE. Conclusions: This report highlights the risk of misdiagnosing PE if relying solely on ELISA D-dimer for exclusion. This report documents the presentation of PE despite having unremarkable ELISA D-dimer measurements and highlights the importance of clinical suspicion.